THE ROLE OF STAKEHOLDERS IN BAIJIU TOURISM IN CHINA: A STAKEHOLDER THEORY PERSPECTIVE - Han , Xue; Tangit, Tania Maria; Mogindol, Spencer Hedley; Suffian, Mohd Firdausi; Chong , Pit Kee (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2025)
Baijiu tourism is an emerging niche sector that serves as a catalyst for regional economic development by integrating local industries, tourism, and cultural heritage that provide dynamic experiences of modern tourism. This study sets the stage for examining Baijiu tourism in the city of Bozhou in Anhui region of China that centred on stakeholder theory which posits that various groups such as local government, Baijiu liquor enterprises, tourism operators, local communities and tourists play pivotal roles in the developing Bozhou as Baijiu tourism hub. Through the identification of their roles and their interactions in promoting Baijiu tourism in Bozhou, value is co-created which emphasizes the active participation of all stakeholders. Another aim to provide insights into the challenges and opportunities inherent in developing a sustainable and culturally rich Baijiu tourism industry in Bozhou. This qualitative exploratory study employs semi-structured interviews to gather in-depth insights from a diverse group of stakeholders through purposive and snowball sampling of 20 participants, comprising 8 females and 12 males volunteers. The data collected is analyzed using thematic analysis, allowing for the identification of patterns, key themes, and underlying narratives within stakeholder perspectives. Findings revealed that stakeholder value matrix mapping is a strategic tool that categorizes stakeholders based on their roles and interactions with one another in the context of developing Baijiu tourism in Bozhou, China. By identifying stakeholders’ roles and understanding their interactions, the matrix provides a clear overview of stakeholder dynamics to foster a collaborative environment. A thorough examination of the challenges and benefits provides a balanced perspective, guiding the development of Baijiu tourism in Bozhou in order for stakeholders to make informed decisions. Balancing the benefits of promoting Baijiu tourism with an awareness of challenges allows the promotion of cultural and economic growth without compromising local heritage or environment.